The Prevalence of Cam Morphology: A Cross-Sectional Evaluation of 3,558 Cadaveric Femora - Hanzlik, Shane; Riff, Andrew J.; Wuerz, Thomas H.; Abdulian, Michael; Gurin, Danielle; Nho, Shane J.; Salata, Michael J. (Frontiers in Surgery, 2021)
Purpose We sought to determine (1) the prevalence of cam deformity in the population and that of bilateral cam deformity, (2) the typical location of a cam lesion, and (3) the typical size of a cam lesion by direct visualization in cadaveric femora. Methods Two observers inspected 3558 human cadaveric femora from the Hamann-Todd osteological collection from the Cleveland Museum of Natural History. Any asphericity greater than 2 mm from the anterior femoral neck line was classified as a cam lesion. Once lesions had been inspected, the prevalence in the population, prevalence by gender, and prevalence of bilateral deformity were determined. Additionally, each lesion was measured and localized to a specific quadrant on the femoral neck based upon location of maximal deformity. Results Cam lesions were noted in 33% of males and 20% of females. Eighty percent of patients with a cam lesion had bilateral lesions. When stratified by location of maximal deformity, 90.9% of lesions were in the anterosuperior quadrant and 9.1% were in the anteroinferior quadrants. The average lesion measured 17mm long x 24mm wide x 6mm thick in men and 14 x 22 x 4 mm in women (p<0.05). Conclusions The population prevalence of cam deformity determined by direct visualization in cadavers may be higher than has been suggested in studies utilizing imaging modalities.